MEKANISME PEMERIKSAAN LAPORAN KEUANGAN PUSAT DAN KEUANGAN DAERAH YANG DILAKUKAN OLEH BADAN PEMERIKSA KEUANGAN (BPK) - Yuliandari, Ni Made; Agung, I Gusti Nyoman (Kertha Negara : Journal Ilmu Hukum; Vol. 01, No. 06, September 2013, 2013)
The Central Government or local governments do accountability report of the implementation of the APBN/APBD for one year review by The Agency of Financial Examiners(BPK). Formulation of the problem raised is : how is the implementation of The Financial Examiner (BPK) in examining the financial statements and financial centre area as well as what are the different types of examinations conducted by BPK. The research is normative law research, with approach militate-invitations and legal analysis, which based on the source of primary law material and secondary law material, as well as analysis by way description and arguments. Based on the discussion of this research, the result is obtained the implementation and the types of conducted by Financial Audit Agency (BPK) to be able to find errors in the management of the state finances of central Government or local governments haave done and can harm the country as well as community.
Keywords: Financial Audit Agency (BPK), Good Governance, Implementation, and Types Checking